Comparison of Whole Life Insurance Premiums Based on the De Moivre Mortality Model and the Indonesian Mortality Table 2019 - Sianturi, Tiurmaida; Siahaan, Linda Natasya; Panjaitan, Sinsi Setiawati (Desimal: Jurnal Matematika, 2026)
This study examines the mathematical structure and sensitivity of whole life insurance premium calculations under two distinct mortality assumptions, namely the De Moivre mortality model and the Indonesian Mortality Table 2019 (TMI 2019). Moving beyond conventional numerical comparisons, this research focuses on identifying structural bias and model-driven deviations in actuarial valuation. A quantitative analytical approach is employed by computing the Net Single Premium (NSP) for entry ages of 25, 30, and 40 years, incorporating variations in the limiting age parameter to evaluate the responsiveness of the De Moivre model. The results demonstrate that the De Moivre model consistently produces higher premiums due to its uniform mortality assumption, which systematically overestimates early-age death probabilities relative to empirical data. Furthermore, the deviation pattern is shown to be non-linear and convergent, where the magnitude of difference decreases with increasing age and limiting age, indicating asymptotic alignment between theoretical and empirical mortality structures. This finding reveals the presence of inherent bias in simplified mortality laws and highlights their limitations in accurately representing real population dynamics. From a mathematical perspective, this study provides a sensitivity-based interpretation of mortality assumptions and establishes a consistent relationship between model structure and premium distortion. Therefore, the results contribute both theoretically, by clarifying the behavior of mortality-based actuarial models, and practically, by informing more reliable model selection in insurance premium estimation.